REHARMONISASI - Daniel Sema (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2017)
When reharmonizing a tune,one gives the melody new color by changing its underlying harmony, that is, the melody remains but the mood of the song changes. Reharmonizing melody is already known since long time. There are also composers who arranged earlier composers’s tunes with the aim to commemorate his works or that tunes sound fresher for listeners today. The commercialization of popular music brought with it an exponential increase in the number of people listening music of all kinds, in dance halls and nightclubs as well as on radio and on recordings. In this atmosphere of popularization, old music has had to struggle for survival. It seems reharmonization is an effort to meet listeners’s taste of music.